Human Computer Interfacing Using Eye Gazing and Movements - Geetha, V; Akshaya, R (International Journal of Computer Sciences and Engineering, 2025)
Eye gaze is staring at the face of others to examine and see what they\'re staring at and to signal interest in interacting. it\'s a nonverbal behaviour wont to convey or exchange info or specific emotions while not the utilization of words. The important aspect of this paper is to give the basic idea of Human Computer Interaction (HCI). The outline of this paper includes the introduction of what exactly are these HCI Systems, current existing systems and recent developments in the field, most common frameworks or architectures used in the design of HCI systems that may include unimodal and multimodal modes, and the applications of HCI